Decision making in adults with autism: The role of ecological executive dysfunctions - García-Villamisar, Domingo; Brand, Matthias; Jodra, Marina (Revista de Psicopatología y Psicología Clínica, 2020)
Abstract: Autism spectrum disorder (ASD) is characterized by presenting problems such as executive dysfunction and behavioral problems. Within the executive functions (EF) a warm area and a cold area can be differentiated; the latter is the most studied, although recent research points to a primary deficit in warm EFs or decision-making in ASD. In the present study, the symptomatology analyzed that accompanies ASD influencing «hot» EFs, or decision-making capacity. The sample consisted of 31 adults with intellectual disability and ASD, with an average mental age of 4.74. Hierarchical multiple regression analyses showed that the executive dysfunction, more specifically the mechanisms of inhibition (impulsive system), was a significant predictor of decision making by adults with ASD. Keywords: Autism spectrum disorder; decision making; executive function; intellectual disability; adults. Toma de decisiones en adultos con autismo: Papel de la disfunción ejecutiva desde una perspectiva ecológica Resumen: El trastorno del espectro del autismo (TEA) se caracteriza por presentar problemas como disfunción ejecutiva y problemas de conducta. Dentro de las funciones ejecutivas (FE) se puede diferenciar el área cálida y el área fría; esta última es la más estudiada, aunque investigaciones recientes apuntan a un déficit primario en las FE cálidas o toma de decisiones en el TEA. En el presente estudio, se analiza la sintomatología que acompaña al TEA que influye en las FE cálidas, o capacidad de toma de decisiones. La población está formada por 31 adultos con discapacidad intelectual y TEA, con una edad mental media de 4.74. Los análisis de regresión múltiple mostraron que la disfunción ejecutiva, más específicamente los mecanismos de inhibición (sistema impulsivo), fue un predictor significativo de la toma de decisiones de los adultos con TEA. Palabras clave: Trastorno del espectro del autismo; toma de decisiones; funciones ejecutivas; discapacidad intelectual; adultos.